Neons fashion LLP (A) : a small seller on Amazon marketplace - Mukherjee, Saral, (SAGE Business. Cases., 2019)
This case provides details of how independent sellers are at the mercy of marketplace operators and ends with the need to review the choices of sales channels for different categories like fashion garments and fashion accessories and for the upcoming launch of kids' shoes.